Pengembangan Media Pembelajaran Interaktif menggunakan Model Pengembangan APPED pada Mata Pelajaran Dasar Desain Grafis untuk Siswa Kelas X Multimedia di SMK Negeri 1 Pasuruan - Eko Cahyo Wahyudi; Satrio Hadi Wijoyo; Tri Afirianto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2022)
During the Covid-19 pandemic, the teaching and learning process was carried out online at SMK Negeri 1 Pasuruan using technology and communication media. The learning media used by teachers to support Basic Graphic Design (DDG) subjects is limited to videos taken from Youtube. The application of learning media that has not been optimal has resulted in student learning outcomes not being able to reach the KKM, so to solve this problem the researcher suggests a solution in the form of developing interactive learning media (MPI) by applying the APPED development model. This model consists of 5 systematic steps, namely initial analysis and research, design, production, evaluation, and dissemination. To develop the MPI, the design is carried out according to the results of the needs analysis. The results of the MPI design include outlines of DDG Basic Competencies 3.2 and 4.2, flowcharts, screen designs, and storyboards. The MPI product developed was validated by 2 media experts, 2 material experts, and 5 students. The results of the MPI validation trial by media experts scored 96%